Incarcerated prolapsed ureterocele complicated by postoperative acute pyelonephritis: a case report - Changchang Hu; LuYang Han; Tian Ding; Zhu Cao; Hangmei Jin; Yinfeng Wang (BMC Urology)
Abstract Background A ureterocele is a cystic dilatation of the terminal ureter that can be located entirely within the bladder or extend into the urethra. In rare cases, female patients may present with a vaginal mass due to prolapse of an ectopic ureterocele and experience urinary incontinence due to laxity of the external urinary sphincter. Case presentation A 37-year-old female presented with a one-year history of recurrent urinary symptoms, including frequent urination, urgency, and dysuria. Over the past two months, she noticed a prolapsed vulvar mass accompanied by urinary incontinence. Three weeks prior to admission, she underwent tension-free vaginal tape–obturator (TVT-O) surgery at another hospital for presumed stress urinary incontinence (SUI). Three days ago, the vulvar mass increased to the size of an egg and could not be manually reduced, accompanied by straining during voiding. Ultrasound and MRI revealed bilateral ureteroceles, with the left ureterocele prolapsed from the bladder to the urethral opening. A diagnosis of ureterocele prolapse with incarceration was made, and the patient underwent manual reduction followed by cystoscopic resection of the left ureterocele. Two days postoperatively, she developed acute pyelonephritis, which was successfully treated with antibiotics. Discussion and Conclusions Prolapsed ureteroceles are a rare condition, and their symptoms can mimic those of SUI, which is typically treated with midurethral sling procedures. However, this treatment approach may inadvertently result in an incarcerated prolapsed ureterocele, requiring urgent medical intervention. This case emphasizes the critical importance of accurate diagnosis of ureteroceles to avoid inappropriate application of midurethral slings and highlights the need for vigilance regarding the potential development of acute pyelonephritis following ureterocele resection.